2020
DOI: 10.1021/acs.iecr.0c00508
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Fabrication of Superhydrophobic Polymeric Surfaces by Polymer Molding Processes

Abstract: Superhydrophobic materials are found in a suite of scientific and industrial applications, and given their broad potential use, there is great interest in facilitating their mass production. Although numerous methods have been used to produce superhydrophobic materials, only a few are capable of fabricating superhydrophobic surfaces and materials at an industrial scale. Techniques such as injection molding, compression molding, hot embossing, and polymer casting play an important role in the mass production of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 122 publications
0
35
0
Order By: Relevance
“…Midtdal et al [120] found that the cleaning effect of this method could last for about 3 to 4 years. The hydrophobic surface is made from polymer layers, which exhibit high initial transmittance [121][122][123][124][125]. Unfortunately, some of these layers are characterized by having high surface energy, which might increase the probability of dust accumulation.…”
Section: Electrodynamic Cleaningmentioning
confidence: 99%
“…Midtdal et al [120] found that the cleaning effect of this method could last for about 3 to 4 years. The hydrophobic surface is made from polymer layers, which exhibit high initial transmittance [121][122][123][124][125]. Unfortunately, some of these layers are characterized by having high surface energy, which might increase the probability of dust accumulation.…”
Section: Electrodynamic Cleaningmentioning
confidence: 99%
“…36 Surface treatments oen refer to silane vapor deposition or liquid cast. [37][38][39][40][41] Surface roughness can be fabricated via colloidal lithography, 42 hot press, [43][44][45] mould, [46][47][48] and selective evaporation. 49 In addition, switchable hydrophilic and hydrophobic patterns have been designed for lotus-like self-cleaning capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…A common method has been the use of a hot molding/embossing technique to pattern polymers and induces surface roughness. 19 Although successful as a nanofabrication technique, complex surface structures are typically quite difficult to obtain without the inclusion of a nanomaterial (particles, fibers, etc.). 20 Issues associated with the viscosity of the molten polymer can often limit material selection, and/or pose challenges when fabricating intricate microstructures, and can require complex and/or multistep fabrication processes.…”
Section: Introductionmentioning
confidence: 99%
“…The use of hydrophobic polymers to fabricate superhydrophobic coatings (directly or as exterior coatings of roughened substrates), including HDPE, has been widely investigated in the literature. A common method has been the use of a hot molding/embossing technique to pattern polymers and induces surface roughness . Although successful as a nanofabrication technique, complex surface structures are typically quite difficult to obtain without the inclusion of a nanomaterial (particles, fibers, etc.)…”
Section: Introductionmentioning
confidence: 99%